2012
DOI: 10.1371/journal.pone.0034364
|View full text |Cite
|
Sign up to set email alerts
|

IL1RL1 Gene Variants and Nasopharyngeal IL1RL-a Levels Are Associated with Severe RSV Bronchiolitis: A Multicenter Cohort Study

Abstract: BackgroundTargets for intervention are required for respiratory syncytial virus (RSV) bronchiolitis, a common disease during infancy for which no effective treatment exists. Clinical and genetic studies indicate that IL1RL1 plays an important role in the development and exacerbations of asthma. Human IL1RL1 encodes three isoforms, including soluble IL1RL1-a, that can influence IL33 signalling by modifying inflammatory responses to epithelial damage. We hypothesized that IL1RL1 gene variants and soluble IL1RL1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 37 publications
3
33
2
5
Order By: Relevance
“…In addition, a recent clinical multicenter cohort study found that human IL1RL1 gene variants and nasopharyngeal IL1RL1-a levels were associated with severe RSV bronchiolitis. The potential biological role of IL1RL1 in the pathogenesis of severe RSV bronchiolitis was supported by high local concentrations of IL1RL1 in children with the most severe disease (16). An important genetic association linking RV with asthma has been identified between host 17q21 locus variants and RV wheezing illness (17).…”
Section: Host Genetic and Familial Determinants Linking Infant Rsv Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent clinical multicenter cohort study found that human IL1RL1 gene variants and nasopharyngeal IL1RL1-a levels were associated with severe RSV bronchiolitis. The potential biological role of IL1RL1 in the pathogenesis of severe RSV bronchiolitis was supported by high local concentrations of IL1RL1 in children with the most severe disease (16). An important genetic association linking RV with asthma has been identified between host 17q21 locus variants and RV wheezing illness (17).…”
Section: Host Genetic and Familial Determinants Linking Infant Rsv Anmentioning
confidence: 99%
“…The GA3 clade has been associated with greater severity of illness compared with clades GA2 and GA4 (41). Differential pathogenesis of RSV A subgroup strains has been reported in an animal model of infection of BALB/cJ mice with RSV A2001/2-20 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). A subgroup strain resulted in greater disease severity, higher lung IL-13 levels, and higher lung gob-5 levels and induced airway mucin expression, supporting differential pathogenicity dependent on strain in these genetically identical mice (42).…”
Section: Viral Strain Determinants Of Infant Infection Severity and Amentioning
confidence: 99%
“…Genetic variation at a number of different loci also contribute to the frequency and severity of the host response to viral infection. 15-18 Finally, the socioeconomic environment may also contribute. 2012 studies showing comparisons of the viral etiology during infancy in children living in the inner-cities of the USA compared to a more suburban environment revealed some interesting differences.…”
Section: Demographicsmentioning
confidence: 99%
“…18 Polymorphisms in IL10, chemokine receptor 5, transforming growth factor β, TLR4, IL13, IL4, and IL-4RA genes are associated with RSV induced bronchiolitis severity. 15 …”
Section: Biomarkersmentioning
confidence: 99%
“…During infection, the airway epithelium is a major source of the "alarmin" cytokine interleukin-33 (IL-33). Intriguingly, nasal aspirates from infants with severe RSV disease have elevated levels of IL-33 (7,8), and variants of the IL-33 receptor gene IL1RL1 are associated with severe RSV disease in human infants (9). Immediately following RSV infection in neonatal mice, a robust IL-33 response is elicited in CD45…”
Section: Epithelial Cellsmentioning
confidence: 99%